Comparative compositions of metabolites and dietary fibre components in doughs and breads produced from bread wheat, emmer and spelt and using yeast and sourdough processes. (16th April 2022) - Shewry, Peter R.; America, Antoine H.P.; Lovegrove, Alison; Wood, Abigail J.; Plummer, Amy; Evans, Jessica; van den Broeck, Hetty C.; Gilissen, Luud; Mumm, Roland; Ward, Jane L.; Proos, Zsuzsan; Kuiper, Petra; et al.
Highlights: Blended grains from varieties of emmer, spelt and bread wheat were compared. Wholemeal flours were processed using sourdough and yeast systems. Flours, doughs and breads were analysed to determine fibre and metabolites. Small differences were observed between the products from the three types of wheat. The greatest differences were between the between sourdough and yeast breads. Abstract: Wholemeal flours from blends of bread wheat, emmer and spelt were processed into bread using yeast-based and sourdough fermentation. The bread wheat flour contained significantly higher concentrations of total dietary fibre and fructans than the spelt and emmer flours, the latter having the lowest contents. Breadmaking using sourdough and yeast systems resulted in changes in composition from flour to dough to bread including increases in organic acids and mannitol in the sourdough system and increases in amino acids and sugars (released by hydrolysis of proteins and starch, respectively) in both processing systems. The concentrations of fructans and raffinose (the major endogenous FODMAPs) were reduced by yeast and sourdough fermentation, with yeast having the greater effect. Both systems resulted in greater increases in sugars and glycerol in emmer than in bread wheat and spelt, but the significance of these differences for human health has not been established.